SPATIAL DISTRIBUTION OF TRACE METALS (Pb, Cr, Cu AND Zn) IN SEDIMENTS OF THE BERAU DELTA, EAST KALIMANTAN AND THEIR ACCUMULATION IN BENTHIC BIOTA - Arifin, Z.; Koesmawati, T. A. (Marine Research in Indonesia, 2007)
Berau delta is a coastal ecosystem where man-made activities are relatively low. The present study has investigated spatial distribution of Pb, Cr, Cu and Zn in sediments and their implication to benthic biota. The result of our study showed that metal concentrations varied from undetected to 55.53 mg kg-1 for Pb and from 3.28 to 22.9 mg kg-1 for Cu, while for Cr and Zn vary from 9.65 to 64.67 mg kg-1 and 10.00 to 1,200 mg kg-1, respectively. The concentrations of Pb, Cu, Cr and Zn in Anadara sp were 7.53 ± 2.06, 4.92 ± 0.55, 1.44 ± 0.12 and 97.87 ± 9.12 mg kg-1 dry weight (dw), respectively. On the other hand, the Pb, Cr, Cu and Zn in Telescopium mauritsi were 4.49 ± 0.03, 0.87 ± 0.05, 259.0 ± 0.01 and 64.78 ± 0.01 mg kg-1 dw, respectively. In conclusion, spatial distribution of trace metals (Pb, Cu, Cr and Zn) in sediments showed that higher concentrations were found in the southern part of the delta, and the accumulation of the metals by mollusk might reflect natural concentrations in biota.